2017
DOI: 10.1016/j.nbd.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Defective axonal transport: A common pathological mechanism in inherited and acquired peripheral neuropathies

Abstract: Peripheral neuropathies are characterized by a progressive and length-dependent loss of peripheral nerve function. This can be caused either by genetic defects, classified as 'inherited peripheral neuropathies', or they can be acquired throughout life. In that case, the disease is caused by various insults such as toxins and mechanical injuries, or it can arise secondary to medical conditions such as metabolic disorders, nutritional deficiencies, inflammation and infections. Peripheral neuropathies are not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 226 publications
0
71
0
Order By: Relevance
“…This is called axonal transport. This transport can also get disrupted due to any injury, genetic disorder, or disease, which may lead to neuropathic pain [41]. Lastly, biochemical processes such as release of cytokines and other inflammatory molecules are also involved in generation of inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…This is called axonal transport. This transport can also get disrupted due to any injury, genetic disorder, or disease, which may lead to neuropathic pain [41]. Lastly, biochemical processes such as release of cytokines and other inflammatory molecules are also involved in generation of inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in axonal transport contribute to many different genetic neuropathies (Prior et al, 2017;Beijer et al, 2019), and its early involvement in disease may be a common driver in peripheral nerve selectivity typical of many forms of CMT2. Indeed, disruption of long-range trafficking has been identified in sensory neurons cultured from CMT2D DRG (Benoy et al, 2018;Mo et al, 2018).…”
Section: Long-range Transport Is Not Universally Impaired In Cmt2d Sementioning
confidence: 99%
“…In vibration-associated neuropathies, conceivable target structures could be peripheral sensory receptors, large or thin myelinated nerve fibers, and small-caliber, nonmyelinated C fibers. Pathological studies by cutaneous biopsy have demonstrated demyelinating neuropathy in the digital nerves of individuals with HAVS [5][6][7][8].…”
Section: Differential Diagnosis In the Whsmentioning
confidence: 99%